Fabry disease: will markers of early disease enable early treatment and better outcomes?. (July 2016) - Hughes, Derralynn A.
Abstract : Purpose of review: This review explores the clinical and pathological features of Fabry disease. New modalities of imaging, biomarkers and long-term treatment effects are discussed. Recent findings: Fabry disease is clinically heterogeneous, and in women the clinical severity has recently been linked to skewing of X-inactivation. Two phenotypes have been described, one with early onset manifestations is including pain and one with later onset single organ manifestations; however, the cardiac outcomes in these two groups appear similar. Fibrosis is found in renal and cardiac tissues on biopsy and appears to be a critical point in the pathology of Fabry disease after which response to enzyme replacement therapy is more limited. In-vitro studies have suggested that lyso-globotriaosylceramide may have an important role in the generation of fibrosis. Imaging, including cardiac magnetic resonance imaging, may have a role in detection of early stages of the disease. Long-term outcomes for patients treated with enzyme replacement therapy are now being described with some suggestion that patients treated at earlier points in the disease course may have better outcomes. Summary: Recent advances in understanding pathology, disease processes and treatment effects may enable future rational targeting of treatment with improved outcomes.